Transparent Gelation of Ionic Liquids Trapped in Silicone Microcup Structures under Scanning Electron Microscopy - Kaede Iwasaki; Masayuki Okoshi (Gels, 2023)
It is expected that ionic liquids will be used in the future as electrolytes for electric double layer capacitors, but currently microencapsulation with a conductive or porous shell is required for their fabrication. Here, we succeeded in fabricating a transparently gelled ionic liquid trapped in hemispherical silicone microcup structures just by observing with a scanning electron microscope (SEM), which allows the microencapsulation process to be eliminated and electrical contacts to be formed directly. To see the gelation, small amounts of ionic liquid were exposed to the SEM electron beam on flat aluminum, silicon, silica glass, and silicone rubber. The ionic liquid gelled on all the plates, and a color change to brown was observed on all the plates except for silicone rubber. This change might be caused by reflected and/or secondary electrons from the plates producing isolated carbon. Silicone rubber could remove the isolated carbon due to the large amount of oxygen inside it. Fourier transform infrared spectroscopy revealed that the gelled ionic liquid included a large amount of the original ionic liquid. Moreover, the transparent, flat gelled ionic liquid could also be made into three-layer structures on silicone rubber. Consequently, the present transparent gelation is suitable for silicone rubber-based microdevices.